2010
DOI: 10.3109/13880209.2010.493179
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of baicalin on carbon tetrachloride induced liver injury by activating PPARγ and inhibiting TGFβ1

Abstract: (2011) Protective effects of baicalin on carbon tetrachloride induced liver injury by activating PPARγ and inhibiting TGFβ1, Pharmaceutical Biology, 49:1, 38-45,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 41 publications
(45 reference statements)
0
23
0
Order By: Relevance
“…In a high-fat diet-induced obesity model of mice, baicalin attenuates liver dysfunction by inhibiting CaMKK/AMPK/ACC pathway and protein kinase B/glycogen synthase kinase 3 beta pathway [15, 16]. Recently, baicalin is shown to protect the carbon tetrachloride-induced liver injury model of the rat by activating PPAR γ and inhibiting TGF β 1 [17]. Here, we demonstrated the protective effect of baicalin in a cholestatic mice model was mediated via NRF2 transcription factor and its downstream target in addition to modulation of oxidative stress-generating enzymes and inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…In a high-fat diet-induced obesity model of mice, baicalin attenuates liver dysfunction by inhibiting CaMKK/AMPK/ACC pathway and protein kinase B/glycogen synthase kinase 3 beta pathway [15, 16]. Recently, baicalin is shown to protect the carbon tetrachloride-induced liver injury model of the rat by activating PPAR γ and inhibiting TGF β 1 [17]. Here, we demonstrated the protective effect of baicalin in a cholestatic mice model was mediated via NRF2 transcription factor and its downstream target in addition to modulation of oxidative stress-generating enzymes and inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…In view of baicalin's serving as a role of PPARγ activator [18], [19], We speculated that baicalin might modulate iNOS expression via activation of PPARγ pathway. SR-202 was used to test this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, baicalin ameliorates experimental chemical colitis [11], [12], [13] and small intestinal injury in severe acute pancreatitis [14], [15]. Baicalin has been reported to repress p38 phosphorylation [16], [17] and activate PPARγ [18], [19] to attenuate inflammation. Therefore, in this experiment we explored whether baicalin would regulate iNOS and NO expression in small intestinal mucosa via modulation of p38 and/or PPARγ pathways in a rat model of acute endotoxemia.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive studies have revealed that baicalin exhibits strong anti-oxidant [11], anti-inflammatory [12], and hepato-protective [13], [14] activities. Baicalin is also a component in a wide range of vegetables, fruits, and beverages derived from plants [15], [16].…”
Section: Introductionmentioning
confidence: 99%